Tree response and mountain pine beetle attack preference, reproduction and emergence timing in mixed whitebark and lodgepole pine stands. (6th August 2015) - Bentz, Barbara J.; Boone, Celia; Raffa, Kenneth F.
Abstract Mountain pine beetle (Dendroctonus ponderosae) is an important disturbance agent in Pinus ecosystems of western North America, historically causing significant tree mortality. Most recorded outbreaks have occurred in mid elevation lodgepole pine (Pinus contorta). In warm years, tree mortality also occurs at higher elevations in mixed species stands. Mountain pine beetle's relative preference for and performance in Pinus species that either commonly or less frequently encounter this insect has received little direct testing. Further, knowledge of the relative proportions of secondary compounds, which can differ among Pinus species and play important roles in attack rates and outcomes, is important to understanding host suitability. We monitored mountain pine beetle attacks, adult emergence timing and reproductive capacity in lodgepole and whitebark (Pinus albicaulis) pines growing in mixed stands at relatively high elevation. Phloem monoterpene chemistry of trees prior to and during attack was compared within and between species. Although beetles attacked lodgepole pine more frequently, lodgepole pines also resisted attacks more frequently. Overall, there were equal numbers of lethal attacks between species. Brood production and adult emergence timing did not differ between tree species. The relative composition of secondary compounds differed by tree species, although both species contained compounds that affect mountain pine beetle attack and reproductive success.